PENGARUH GOOD CORPORATE GOVERNANCE, KARAKTERISTIK, DAN ATRIBUT AUDIT PERUSAHAAN TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN - Shagan, Jessieca (Ma Chung Press, 2022)
The purpose of this study is to analyze the effect of good corporate governance, characteristics, and audit attributes on the disclosure of company risk in the mining sector listed on the Indonesia Stock Exchange in 2019-2021. Risk disclosure is believed to have a role in increasing the credibility of the company's financial reporting and to assist investors in understanding the company's business strategy by obtaining broad information, especially related to risk information. The sampling technique was purposive sampling and obtained 21 companies with a research period of 3 years. The data analysis method used is multiple linear regression analysis using the Statistical Package for Social Science (SPSS) version 20. The theoretical basis used in this research is signaling theory and stakeholder theory. Good corporate governance is assessed using the variables of public ownership, independent commissioners, and audit committees. Company characteristics are assessed using profitability and leverage variables. While the audit attributes are assessed based on the quality of the external auditor. This study uses the voluntary risk disclosure standard developed by Mokhtar & Mellet (2013) which amounts to 40 items and is calculated using the content analysis method. The results showed that only leverage have significant effect on the company's risk disclosure. Meanwhile, public ownership, independent commissioners, audit committees, profitability, and quality of external auditors had no significant effect on the company's risk disclosure.